Bina’ Syakhsiyah Mahasiswa Pendidikan Biologi Melalui Kegiatan Praktikum - Aisyah Idris; Eva Nauli Taib; Maqfirah Maqfirah (Universitas Islam Negeri Ar-Raniry, 2019)
This study aims to determine the character values in laboratory activities, the process of character building and to find out the causes of the reduced character values of biology education students. The method used is the triangulation method. Data collection is done by observation, in-depth interviews and distributing questionnaire sheets. The results showed the lowest character value criteria was honesty, that wasin enough category with an average score of 3.32. It can be concluded that the overall character values of biology education students are classified as good with an average value of 3.55. Although the process of character building for biology education students through laboratory activities has been carried out by providing punishment and rewards, there are reduced character values due to insufficient face-to-face time in laboratory activities, lack of cooperation among assistants, and students’ lack of awareness to obey the rules, self-introspection and motivation.